2005
DOI: 10.1002/nau.20122
|View full text |Cite
|
Sign up to set email alerts
|

Rho‐kinase inhibition suppresses bladder hyperactivity in spontaneously hypertensive rats

Abstract: Overexpression of RhoA may play a role in hypertension-related OAB. Inhibition of Rho-kinase activity with Y-27632 produced a significant suppression of bladder overactivity. Identification of Rho-kinase isoforms that are bladder-tissue specific and their selective inhibitors may help to disassociate the unwanted hypotensive effects of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
2
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 32 publications
(51 reference statements)
7
63
2
1
Order By: Relevance
“…This is in agreement with previous work wherein identification of these proteins has also been demonstrated [25,27,30,31,37,45]. In addition, recent reports demonstrate that ROKβ is partly responsible for the high degree of force maintenance in the detrusor smooth muscle in overactive bladders [30][31][32]. Our experiments revealed that both ROKα and ROKβ are expressed at lower levels in the urethra compared to the detrusor and trigone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous work wherein identification of these proteins has also been demonstrated [25,27,30,31,37,45]. In addition, recent reports demonstrate that ROKβ is partly responsible for the high degree of force maintenance in the detrusor smooth muscle in overactive bladders [30][31][32]. Our experiments revealed that both ROKα and ROKβ are expressed at lower levels in the urethra compared to the detrusor and trigone.…”
Section: Discussionsupporting
confidence: 93%
“…In human, rat, rabbit and guinea pig bladder, the Rho-kinase pathway represents an important regulator of smooth muscle activity and tone [25,[27][28][29][30][31][32]. The prototype Rho-kinase inhibitor Y-27632 has been shown to attenuate contractions of bladder smooth muscle evoked by CCh, through the decrease of Ca 2+ sensitivity of the contractile apparatus [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Wibberley et al 22 found that Rhokinase inhibitors (Y-27632, HA 1077) reduced basal tension of isolated bladder preparations. Furthermore, Rajasekaran et al 23 showed that Rho kinase inhibition reduced DO in spontaneous hypertensive rats.…”
Section: Spontaneous Activation Of the Myocytementioning
confidence: 99%
“…Overexpression or sensitization of muscarinic receptors was noted as the mechanism (Schneider et al, 2005). Moreover, intracellular calcium sensitization (Sherer et al, 2000;Rajasekaran et al, 2005) and correlation of autonomic nerve alteration (Steers et al, 1999) were also hypothesized.…”
mentioning
confidence: 99%